Fertilization analysis in the corn agroecosystem in the Papaloapan basin - López Escudero, Roberto de Jesús; López Romero, Gustavo; Lango Reynoso, Verónica; Inurreta Aguirre, Héctor Daniel (Revista Mexicana de Ciencias Agrícolas, 2023)
Corn is the main crop of the basic basket in Mexico and one of the products of greatest commercial and economic importance nationwide. Among the main factors of agronomic management that determine its level of productivity is fertilization. Currently, as a result of the armed conflicts between Russia and Ukraine, there is a shortage and, consequently, a rise in the price of fertilizers. Therefore, this work studied the fertilization factor in the Papaloapan basin to analyze the effect of chemical nutrition on the corn crop based on its productivity in t ha-1 of grain. Three fertilization scenarios were simulated with the use of the SWAT model, and the results of the factors were mapped by statistically analyzing the difference in means of the treatments through an Anova, which yielded a value of P= 2e-16, showing a significant difference in the effects of the factors analyzed on the yield of the crop. In conclusion, the fertilization factor was higher than the non-fertilization factor, with a difference between means of 7.8 t ha-1 of grain, which indicates that the absence of fertilization work of the crop negatively impacts the productivity of corn grain. Nonetheless, the efficiency between half and full doses of nitrogen fertilization in terms of yield was found to be similar, with the half-dose factor being more efficient than the previous one.